PENGEMBANGAN E-BOOK MATERI SISTEM REPODUKSI MANUSIA TERINTEGRASI PENDIDIKAN KARAKTER BERBASIS APLIKASI SMART APPS CREATOR (SAC) KELAS IX SMPS /MTS - Afifah Nurul Humam; Mukhlis Rohmadi; Sondra Swestyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2023)
This research is a Research and Development research (research and development) with a 4D development model (define, design, develop, and disseminate). The purpose of this study was to determine the validity and response of teachers and students to the development of e-Book material of human reproductive system integrated character education with SAC application-based. Data collection was carried out by distributing questionnaires, interviews, and observations to teachers and 13 students at MTs Nurul Yaqin Kuala Kurun. The instruments used in this study were validation questionnaires, teacher and student response questionnaires, teacher and student response questionnaires to students' religious values and healthy lifestyles, and observation sheets. The data from the material expert validation results obtained a very valid category of 3.78, design expert validation with a valid category of 3.31, character education expert validation with a very valid category of 3.63. The results of the teacher's response obtained a very valid category of 3.66 and a student's response with a very valid category of 3.67. The results of teacher responses to religious values and healthy lifestyles of students obtained a good category of 3.00 and student responses with a very good category of 3.54, the results of teacher and student interviews showed a relationship between teacher and student response questionnaires with interview results, and the results of observations obtained a very good category of 95%. Thus, it can be concluded that the development of e-Book material for the integrated human reproductive system of Smart Apps Creator (SAC) application-based character education is valid, practical, and can maximize the religious value and healthy lifestyle of students.